Accumulative Roll Bonding for Improvement mechanical properties of Aluminum based Composite - Agus Pramono (INSIST, 2018)
The Aluminum has special properties such as light weight, ductile and a lower melting point. It has very suitable for applied as composite material, with ceramic as reinforcement. Accumulative roll bonding (ARB) is part of technology of Severe Plastic Deformation (SPD) that has been developed of manufacturing process for metals, alloys and composites as well. It has a potential becoming an industrial process to produce composite and ultrafine-grained (UFG) metal sheets. In this research, the development of aluminum-based composites is made by SPD technology using the ARB method on aluminum plate sheets with boron carbide (B4C) as reinforcement, is expected to improve its mechanical properties along with the rules of microstructure analysis. To get of the UFG metallic materials where the mean grain size must be smaller than 1μm are expected can be exhibit excellent mechanical properties. The ARB process consists of multiple cycles of rolling, cutting, stacking and solid-state deformation bonding. Two plates were prepare for the ARB sample process, cleaning uses acetone liquid to prevent attachment of dust and dirt on the surface to be made in contact with other samples. Acetone and grinding to produce a rough surface to facilitate the surface binding process between samples, B4C powder is sprinkled between the centers of aluminum plate surface and stacked going together.